2017
DOI: 10.1002/jcp.25873
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and adenosine receptors in the immunopathogenesis and treatment of cancer

Abstract: Tumor cells overcome anti-tumor responses in part through immunosuppressive mechanisms. There are several immune modulatory mechanisms. Among them, adenosine is an important factor which is generated by both cancer and immune cells in tumor microenvironment to suppress anti-tumor responses. Two cell surface expressed molecules including CD73 and CD39 catalyze the generation of adenosine from adenosine triphosphate (ATP). The generation of adenosine can be enhanced under metabolic stress like tumor hypoxic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 277 publications
(317 reference statements)
2
92
0
Order By: Relevance
“…Because this receptor recruits cAMP as a secondary messenger (Kazemi et al, ) we used CGS 21680 agonist to evaluate A2aR functionality by measuring cAMP in MIN6 cells. The EC50 value for this agonist has been calculated 2.4 µM.…”
Section: Resultsmentioning
confidence: 99%
“…Because this receptor recruits cAMP as a secondary messenger (Kazemi et al, ) we used CGS 21680 agonist to evaluate A2aR functionality by measuring cAMP in MIN6 cells. The EC50 value for this agonist has been calculated 2.4 µM.…”
Section: Resultsmentioning
confidence: 99%
“…8 Accumulating evidences have revealed that A2A receptors respond to the adenosine stimulation and thus modulate multiple physiological and pathophysiological processes including memory formation, emotionstate alteration, inflammatory reaction, immune regulation, braininjury repair, and aging process. 9,10 Recent researches have revealed that elevated adenosine levels in extracellular tumor Abbreviations: BBB, blood-brain barrier; LDH, lactate dehydrogenase; SDF-1, Stromal cell-derived factor-1. microenvironment and the activation of A2A receptors contribute to the immune escape and promote the progression and metastasis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that our SLICE screening platform also could be used to identify gene deletions that allow T cells to escape various forms of suppression. We focused on adenosine, a key immunosuppressive factor in the tumor microenvironment (Allard et al, 2017;Beavis et al, 2017;Kazemi et al, 2018). We performed a genome-wide proliferation screen by stimulating T cells in the presence of an adenosine receptor 2 (A2A) agonist (CGS-21680) at a suppressive dose of 20µM ( Figure S6A) versus a vehicle control for four days (Jacobson and Gao, 2006).…”
Section: Slice Screen For Resistance To Immunosuppressive Adenosine Smentioning
confidence: 99%